2010
DOI: 10.3109/09513590.2010.493961
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum and follicular fluid SHBG levels andSHBG(TAAAA)npolymorphism with follicle size in women undergoing ovarian stimulation

Abstract: SHBG levels and the SHBG (TAAAA)(n) polymorphism are associated with follicle size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
0
23
0
1
Order By: Relevance
“…Physical examination was performed. All women of the study population underwent a long GnRH agonist stimulation protocol as previously described [19]. Oocytes were retrieved by follicle aspiration by the transvaginal route under ultrasound guidance and the follicles were stratified into two groups according to their diameter (small follicles with diameter ≤12 mm and large follicles with diameter ≥18 mm).…”
Section: Subjectsmentioning
confidence: 99%
“…Physical examination was performed. All women of the study population underwent a long GnRH agonist stimulation protocol as previously described [19]. Oocytes were retrieved by follicle aspiration by the transvaginal route under ultrasound guidance and the follicles were stratified into two groups according to their diameter (small follicles with diameter ≤12 mm and large follicles with diameter ≥18 mm).…”
Section: Subjectsmentioning
confidence: 99%
“…All women of the study population underwent a long GnRH agonist stimulation protocol as previously described [24]. Conventional IVF was performed in all couples.…”
Section: Subjectsmentioning
confidence: 99%
“…Previous studies of our group have shown significant associations of FSHR 307(T/A)/FSHR 680(N/S), SHBG (TAAAA) n and CYP19(TTTA) n polymorphisms with the ovarian response to standard gonadotrophin stimulation [11][12][13]. The aim of the current study was to investigate the potential synergistic effect of the above polymorphisms on the follicular numbers and size, the oocyte numbers, the serum hormone levels and the pregnancy rate of women undergoing FSH stimulation for in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI), due to tubal or male infertility factor.…”
Section: Introductionmentioning
confidence: 70%
“…All women of the study population underwent a long GnRH agonist stimulation protocol as previously described [11,14]. Oocytes were retrieved by follicle aspiration by the transvaginal route under ultrasound guidance and the follicles were stratified into two groups according to their diameter (small follicles with diameter ≤12 mm and large follicles with diameter ≥18 mm).…”
Section: Methodsmentioning
confidence: 99%